Metallic glass composite
By preparing thermally sprayed glass powder with thermal expansion rate corresponding to the metal substrate and adjusting the composition of the glass material, the difference in thermal expansion rate and bubble problems when thermal sprayed glass is adhered to the metal substrate, and the impact resistance and adhesion strength of the metal glass composite are improved.
Patent Information
- Application Number
- CN202480002728.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-04
- Filing Date
- 2024-06-14
- Publication Date
- 2025-03-04
AI Technical Summary
When the prior art adheres glass to a metal substrate by thermal spraying, it is difficult to control the difference in thermal expansion ratio between the metal substrate and the thermally sprayed glass powder, resulting in a decrease in adhesion and inevitably generate air bubbles, reducing the impact resistance of the metal glass composite.
Prepare thermally sprayed glass powder with thermal expansion rate corresponding to the metal substrate, and adjust the composition of the glass material to control the number of bubbles in the glass formed after thermal spraying, thereby improving the impact resistance of the metal glass composite.
By adjusting the thermal expansion rate and composition of the glass material of the thermal sprayed glass powder, the impact resistance and adhesion strength of the metal glass composite were successfully improved, and the differences in thermal expansion rate and bubble problems were solved.
Smart Images

Figure CN119562935A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a metal glass composite, and more particularly to a metal glass composite in which glass particles are thermally sprayed onto a metal surface and firmly adhered thereto. Background Art
[0002] When a glassy film is formed on a metal substrate, a thermal spraying method is used. When a glassy film is formed by thermal spraying, the glassy film is formed by bonding the glassy film to the metal substrate more firmly than enamel. Therefore, thermal spraying is suitable for applications that require durability.
[0003] In a thermal spraying device, a thermal spraying material such as glass or ceramic is mixed with a carrier gas. A separately supplied gas and high current generate plasma, which becomes highly heated, and the thermal spraying glass powder composed of glass particles is melted. Then, the molten thermal spraying glass powder is sprayed from the thermal spraying device toward the metal substrate of the thermal spraying object (see Patent Documents 1, 2, etc.).
[0004] The metal substrate and the glass powder of thermal spraying have different thermal expansion coefficients (linear expansion coefficients). Based on the relationship of specific heat, the metal substrate is cooled rapidly. Since the volume shrinkage rate between the metal substrate and the thermal spraying glass powder is different, the expansion coefficient needs to be controlled, and the thermal spraying of different types of materials is extremely difficult.
[0005] The inventors have developed a thermal spraying glass powder and a thermal spraying method disclosed in Patent Document 1 and a thermal spraying device disclosed in Patent Document 2. The inventors have established a strong thermal spraying between a metal substrate of different materials and the glass of the thermal spraying glass powder, and have successfully manufactured a metal glass composite. According to the disclosure of Patent Document 1, the surface of the metal substrate of the thermal spraying object is roughened by sandblasting or the like and then heated. Then, the glass derived from the thermal spraying glass powder melted by thermal spraying forms a film on the surface. It is believed that the glass derived from the thermal spraying glass powder penetrates into the surface of the metal substrate thus roughened, thereby improving the adhesion between the metal substrate and the glass.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2013-216977
[0009] Patent Document 2: Japanese Patent Application Publication No. 2021-130841 Summary of the invention
[0010] Technical issues to be solved by the invention
[0011] Afterwards, the inventors repeatedly conducted in-depth research on forming glass on the surface of a metal substrate by thermal spraying. As a result, the inventors found that the thermal expansion coefficient of the thermal sprayed glass powder needs to be adjusted according to the type of the metal substrate due to the difference in thermal expansion coefficient. In addition, the inventors found that the bubbles that are inevitably generated when the thermal sprayed glass powder is melted by thermal spraying and adhered to the metal substrate will reduce the impact resistance of the glass of the formed metal glass composite.
[0012] The present invention has been made in view of the above-mentioned points, and provides a metal glass composite which can prepare a thermally sprayed glass powder having a thermal expansion coefficient corresponding to that of a metal substrate to be thermally sprayed, and which suppresses bubbles contained in the glass formed on the metal substrate after thermal spraying to improve strength such as impact resistance, wherein the metal glass composite is formed by integrating a metal substrate of different materials and the glass of the thermally sprayed glass powder by thermal spraying.
[0013] Means for solving technical problems
[0014] That is, the metallic glass composite of the embodiment is characterized by comprising: a metal base material portion composed of a body-centered cubic iron material; and a thermally sprayed glass portion formed on the metal base material portion with a film thickness of 10 to 2000 μm, wherein in the glass material forming the thermally sprayed glass portion, Si is used as a first component (A). O2: 35-70 mass %, as the second component (B), B2O3: 9-15 mass %, Li2O: 5-9 mass % and Na2O: 4-10 mass % are set to a total of 18-30 mass %, as the third component (C), BaO: 0-15 mass %, TiO2: 2-15 mass %, Al2O3: 0-8 mass % and ZnO: 0-15 mass % are set to a total of 10-30 mass %, as the main component (D) composed of the total of the first component (A), the second component (B) and the third component (C), the glass material contains 90 mass % or more, and the value of the linear expansion coefficient of the glass material from room temperature to 300°C is 9-11 (×10 6 / °C), and the area ratio of bubbles larger than 1 μm in the cross section in the thickness direction of the thermal sprayed glass portion was less than 40%.
[0015] The metallic glass composite of the embodiment is characterized in that it comprises: a metal base material portion composed of a face-centered cubic iron material; and a thermal sprayed glass portion formed on the metal base material portion with a film thickness of 10 to 2000 μm, wherein the glass material forming the thermal sprayed glass portion has S as a first component (A). As the second component (B), the total of B2O3: 2-8 mass%, Li2O: 8-15 mass% and Na2O: 8-20 mass% is set to 25-35 mass%, as the third component (C), the total of BaO: 3-12 mass%, TiO2: 4-15 mass%, Al2O3: 0-5 mass% and ZnO: 0-5 mass% is set to 10-20 mass%, as the main component (D) composed of the total of the first component (A), the second component (B) and the third component (A), it contains 90 mass% or more, and the value of the linear expansion coefficient of the glass material from room temperature to 300°C is 14-17 (×10 6 / °C), and the area ratio of bubbles larger than 1 μm in the cross section in the thickness direction of the thermal sprayed glass portion was less than 40%.
[0016] Furthermore, the difference between the linear expansion coefficient of the glass material of the metallic glass composite and the linear expansion coefficient of the metal substrate portion may be within 15%.
[0017] Furthermore, the metallic glass composite may include a melt-solidified portion at a boundary between the metal base portion and the thermally sprayed glass portion in a cross section, wherein the thermally sprayed glass portion is embedded in the metal base portion, and the melt-solidified portion may have a thickness of 0.3 μm or more.
[0018] Furthermore, in the thermal sprayed glass portion of the metallic glass composite, the area ratio of bubbles of 1 μm or larger existing in a region within 30% of the boundary between the metal substrate portion and the thermal sprayed glass portion in the thickness direction of the thermal sprayed glass portion starting from the boundary may be 50% or less.
[0019] Furthermore, the thickness of the thermal sprayed glass portion of the metallic glass composite may be 10 to 100 μm, and the area ratio of bubbles larger than 1 μm in a cross section in the thickness direction of the thermal sprayed glass portion may be less than 10%.
[0020] Furthermore, the components other than the main component (D) in the glass material of the metallic glass composite may be auxiliary components (E), and the auxiliary components (E) may be CaO, SrO, MgO, P2O5, K2O, V2O5, Cr2O3, MnO2, Fe2O3, Co3O4, NiO2, CuO, Y2O3, ZrO2, Nb2O2, MoO3, SnO2, Sb2O3, WO3, PbO, Bi2O3, La2O3, CeO2, Pr6O 11, any one or more of Nd2O3, Sm2O3, and Gd2O3.
[0021] Effects of the Invention
[0022] The metallic glass composite of the present invention is a metallic glass composite formed by integrating a metal substrate of different materials and the glass of thermal spraying glass powder by thermal spraying, and can prepare a thermal spraying glass powder having a thermal expansion coefficient corresponding to the metal substrate as the thermal spraying object, and can suppress bubbles contained in the glass formed on the metal substrate after thermal spraying to improve strength such as impact resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The following are schematic cross-sectional views of (A) a plate material, (B) a plate material with a hole, (C) a tube material, and (D) a bolt material related to the metal glass composite.
[0024] Figure 2 (A) is a schematic diagram showing the composition relationship of glass materials, and (B) is a schematic cross-sectional diagram showing the structure of a metallic glass composite.
[0025] Figure 3 (A) is a 100-fold magnified cross-sectional photograph, and (B) is a 1000-fold magnified cross-sectional photograph of the metallic glass composite of the trial example code G1.
[0026] Figure 4 (A) is a 100-fold magnified cross-sectional photograph, and (B) is a 1000-fold magnified cross-sectional photograph of the metallic glass composite of the trial example code G2.
[0027] Figure 5 (A) is a 100-fold magnified cross-sectional photograph and (B) is a 1000-fold magnified cross-sectional photograph of the glass material of the metallic glass composite of Trial Example Code G6.
[0028] Figure 6 (A) is a 100-fold magnified cross-sectional photograph and (B) is a 1000-fold magnified cross-sectional photograph of the glass material of the metallic glass composite of Trial Example Code G11.
[0029] Figure 7 (A) is a 100-fold magnified cross-sectional photograph and (B) is a 1000-fold magnified cross-sectional photograph of the glass material of the metallic glass composite of the trial example code G13.
[0030] Figure 8 (A) is a 100-fold magnified cross-sectional photograph and (B) is a 1000-fold magnified cross-sectional photograph of the glass material of the metallic glass composite of Trial Example Code G19.
[0031] Fig. 9(A) is a 100-fold magnified cross-sectional photograph and (B) is a 1000-fold magnified cross-sectional photograph of the glass material of the metallic glass composite of Trial Example No. H5.
[0032] Fig.10 This is a graph showing the relationship between the area ratio of the total bubbles and the height of the falling ball.
[0033] Fig.11 This is a graph showing the relationship between the area ratio of bubbles in the boundary portion and the dielectric strength. DETAILED DESCRIPTION
[0034] The metal glass composite of the embodiment is a composite of metal and glass having a glassy coating on the whole or part of the surface of various forms of metal by thermal spraying. The glassy substance is prepared into a powder such as a frit and supplied to a thermal spraying device. Then, the glassy powder is instantly melted by plasma thermal spraying of the thermal spraying device and sprayed toward the metal substrate portion as the target. As a result, the molten glassy substance adheres to the metal substrate portion and is cooled, and the glassy substance is fixed to the metal and integrated.
[0035] Figure 1 Schematic diagrams (A) to (D) are schematic diagrams of metal glass composites 1A, 1B, 1C, and 1D in which a thermally sprayed glass portion 20 is formed on (on the surface of) a metal base portion 10 .
[0036] Figure 1 (A) is a metal glass composite 1A in which a thermally sprayed glass portion 20 is formed on the surface of a sheet metal metal substrate portion 11 (10). The thermally sprayed glass portion 20 is formed on the surface of a metal substrate portion 11 such as a steel plate by thermal spraying. As a result, the steel plate is given impact resistance, corrosion resistance, etc. Figure 1 In (B), a sheet metal-like metal base material part 12 (10) having a hole part 15 for fixing with bolts, rivets, etc. and connecting with other parts is prepared, and the metal-glass composite 1B is formed with a thermally sprayed glass part 20 on the surface of the metal base material part 12. The thermally sprayed glass part 20 is also adhered to the hole part 15 and the periphery of the hole part 15, so that the resistance to wear, corrosion, etc. caused by contact between metals can be improved.
[0037] Figure 1 (C) is a metal glass composite 1C in which a thermally sprayed glass portion 20 is formed on the surface of a metal base material portion 13 (10) of a tube material. In the case of the metal glass composite 1C, it is possible to form an electrode for silent discharge by combining with an electrode of another cylindrical body (see Patent Document 1, etc.). The insulating performance generated by the glass quality of the thermally sprayed glass portion 20 can be utilized. Figure 1In (D), a bolt is used as the metal base material portion 14 (10). By forming a thermal sprayed glass portion 20 on the surface of the bolt, the corrosion resistance of the bolt is improved, and the resistance to brittleness caused by corrosion and fracture of the bolt is improved. Of course, Figure 1 The disclosure of the metallic glass composite is merely an example, and the metallic glass composite is not limited to the illustrated embodiment.
[0038] In the metal glass composite of the embodiment, the thickness of the thermal sprayed glass part 20 is in the range of 10 to 2000 μm. When the thickness of the thermal sprayed glass part 20 is less than 10 μm, the molten glass tends to form stripes or spots on the surface of the metal substrate part 10. Therefore, it is easy to make the glass adhesion and homogenization difficult. In addition, when the thickness of the thermal sprayed glass part 20 exceeds 2000 μm, the thickness of the thermal sprayed glass part 20 becomes too large, and cracking and peeling are easy to occur due to the difference in thermal expansion coefficient between the metal substrate part 10 and the thermal sprayed glass part 20. In particular, as described later, it becomes more difficult to control the bubbles contained in the thermal sprayed glass part 20.
[0039] When preparing the metallic glass composite of the embodiment, the composition of the glass material constituting the thermal sprayed glass portion is determined by the difference in thermal expansion coefficient (linear expansion coefficient) based on the type of metal of the metal base material portion, especially based on the type of iron material (iron alloy). The metallic glass composite of the embodiment mainly uses body-centered cubic iron material and face-centered cubic iron material as the metal base material portion.
[0040] Body-centered cubic iron materials are martensitic stainless steel, ferritic stainless steel, etc., such as stainless steels such as SUS409, SUS420, SUS430, and general structural rolled steels such as SS400. In the examples described below, SUS409 and SS400 are used. Face-centered cubic iron materials are austenitic stainless steels such as SUS304, SUS310, SUS316, etc. In the examples described below, SUS304 is used.
[0041] In order to correspond to the metal type of the metal base material portion, it is necessary to adjust the composition of the glass material constituting the thermal sprayed glass portion. Figure 2The schematic diagram of (A) shows an overview of the composition of the glass material constituting the thermal sprayed glass portion. First, the main component (D) is composed of the first component (A), the second component (B) and the third component (C). In the unit weight of the glass material, the main component (D) is more than 90 mass %. In addition, as the remaining component of the glass material, an auxiliary component (E) is mixed. Of course, unavoidable impurity components may be mixed into the glass material. Hereinafter, mass % and weight % will be regarded as synonyms. The ratio of mass % between the first component (A), the second component (B) and the third component (C) mainly varies depending on the iron material of the body-centered cubic system or the iron material of the face-centered cubic system.
[0042] The first component (A) is SiO2. The SiO2 of the first component (A) is the main component of the glass material constituting the thermal sprayed glass part, and mainly improves corrosion resistance, hardness (wear resistance), antifouling property, electrical insulation, withstand voltage, etc. In the case of a metal substrate part of a body-centered cubic iron material, 35 to 70% by mass is mixed in the glass material. And in the case of a metal substrate part of a face-centered cubic iron material, 50 to 60% by mass is mixed in the glass material.
[0043] When the blending ratio of SiO2 of the first component (A) is lower than the respective lower limits, the corrosion resistance and other properties of the finally formed thermal sprayed glass part will be reduced. In addition, changes over time such as whitening of the thermal sprayed glass part are likely to occur. When the blending ratio of SiO2 of the first component (A) exceeds the respective upper limits, the surface of the thermal sprayed glass part formed after thermal spraying is difficult to become flat. During thermal spraying, the metal substrate part that is the object of thermal spraying is heated to a temperature above the thermal deformation temperature (above 1000°C). As the amount of SiO2 increases, the refractoriness of the glass material itself increases, and the solubility during plasma thermal spraying decreases. Therefore, the load on the thermal spraying device increases, and it is difficult to obtain the smoothness of the thermal sprayed glass part after melting.
[0044] Compared with the components described below, the thermal expansion coefficient of SiO2 is relatively small. An increase in the amount of SiO2 will reduce the thermal expansion coefficient of the entire glass material. In addition, the melting property during plasma thermal spraying is low, resulting in high viscosity. Therefore, SiO2 needs to consider the adjustment of the thermal expansion coefficient of the metal substrate part of the body-centered cubic iron material or the adjustment of the thermal expansion coefficient of the metal substrate part of the face-centered cubic iron material, corrosion resistance, and ease of thermal spraying and melting. In addition, considering the adjustment of the thermal expansion coefficient, the amount of SiO2 added to the glass material is specified according to the composition of the aforementioned metal substrate part.
[0045] The second component (B) is a component that mainly adjusts the solubility and low viscosity of the glass material during melting, and is a component containing B2O3, Li2O, and Na2O. The amount of the second component (B) as a whole and the amount of each component contained in the second component (B) are adjusted and blended so that the thermal expansion coefficient of the glass material is close to the thermal expansion coefficient of the metal substrate.
[0046] B2O3 promotes the melting and low viscosity of glass materials during plasma thermal spraying. Therefore, it is indispensable in adjusting the effects of SiO2 and other components. The thermal expansion coefficient of B2O3 is as small as that of SiO2. However, in contrast to SiO2, B2O3 reduces corrosion resistance, hardness (wear resistance), electrical insulation, and voltage resistance, and promotes changes over time. As a result, the increase in B2O3 will damage the properties of the thermally sprayed glass portion. B2O3 is easily volatilized by heating during thermal spraying, and the volatilization amount is not easy to control. As B2O3 volatilizes, the thermal expansion coefficient of the glass material originally designed will change.
[0047] In the case of a metal substrate portion of an iron material of a body-centered cubic system, 9 to 15% by mass of B2O3 is mixed into the glass material. In addition, in the case of a metal substrate portion of an iron material of a face-centered cubic system, 2 to 8% by mass of B2O3 is mixed into the glass material. When the mixing ratio of B2O3 exceeds the upper limit, peeling and penetration (cracking) of the glassy film of the thermally sprayed glass portion formed on the surface of the metal substrate portion are likely to occur. When the mixing ratio of B2O3 is lower than the lower limit, the melting property and low viscosity of the glass material during plasma thermal spraying cannot be fully utilized, and it cannot become a suitable glass material.
[0048] Li2O is an indispensable component in adjusting the effects of SiO2 and other components in order to promote the melting and low viscosity of the glass material during plasma thermal spraying. At the same time, Li2O is relatively non-volatile during plasma thermal spraying, and has the largest thermal expansion coefficient compared to other components. Therefore, Li2O can achieve the adjustment of the thermal expansion coefficient with other components, and also plays a role as a buffer material in terms of the properties of the glassy film of the desired thermal sprayed glass part. Li2O will reduce the corrosion resistance and hardness (wear resistance) against acids and alkalis. Moreover, the glass material in thermal spraying is easy to recrystallize (lithium silicate crystals). With recrystallization, corrosion resistance and the like will be further improved, but the thermal expansion coefficient of the glassy film formed by recrystallization will be reduced. The reduction of this thermal expansion coefficient is difficult to control, and as a result, it becomes the cause of penetration (cracking) of the surface of the coated object.
[0049] In the case of a metal substrate portion of a body-centered cubic iron material, 5 to 9 mass % of Li2O is mixed into the glass material. In addition, in the case of a metal substrate portion of a face-centered cubic iron material, 8 to 15 mass % of Li2O is mixed into the glass material. When the mixing ratio of Li2O exceeds the upper limit, in addition to the aforementioned problems such as peeling, the reduction of electrical insulation, voltage resistance, corrosion resistance, etc. will also become significant. When the mixing ratio of Li2O is lower than the lower limit, the melting property and low viscosity during plasma thermal spraying will not be manifested.
[0050] According to the amount of admixture occupied in the glass material, Na2O improves the fusibility of the glass material during plasma thermal spraying, and at the same time increases the viscosity during melting. Thus, the glass material thermally sprayed to the surface of the metal substrate part as the thermal spraying object is easy to adhere to the surface of the metal substrate part, which can improve the adhesion strength between the thermal sprayed glass part and the surface of the metal substrate part. In addition, as the viscosity of the glassy material generated by Na2O increases, the fluidity of the molten glass material itself adhered to the surface of the metal substrate part will be slightly reduced, so the movement of the bubbles involved in the thermal spraying (due to fluidity, the bubbles gather and become larger) will also be suppressed (refer to the embodiment described later). Na2O greatly helps to improve the smoothness of the thermal sprayed glass part after plasma thermal spraying, reduce its film thickness, and improve electrical insulation and voltage resistance. In addition, Na2O will improve electrical insulation and voltage resistance when it is in the same mass ratio (weight ratio) as Li2O, and is also excellent in function.
[0051] The thermal expansion coefficient of Na2O is second only to Li2O, so the thermal expansion coefficient of the glass material is easily designed according to the thermal expansion coefficient of the material of the individual metal substrate part such as the metal substrate part of the body-centered cubic iron material or the metal substrate part of the face-centered cubic iron material as the thermal spraying object. In this case, the amount of Na2O added depends on the amount ratio with Li2O. And, as a matter to be noted, the viscosity of the melt manifested by the addition of Na2O has a different property from the viscosity of the melt manifested by the addition of Al2O3 and CaO described later. In the case of Na2O, as the amount of its addition increases, there is a tendency that the viscosity of the melt increases approximately linearly. On the other hand, in the case of Al2O3 and CaO, the viscosity of the melt changes sharply according to the amount of its addition. Therefore, Na2O is suitable in terms of the ease of viscosity control when the glassy material is melted.
[0052] However, Na2O is easily volatilized by plasma thermal spraying like B2O3, and the volatilization amount is larger than that of Li2O. The thermal expansion coefficients of Na2O and B2O3 are greatly different. Therefore, in the case of a metal base material part of a body-centered cubic iron material, 4 to 10 mass% of Na2O is mixed in the glass material. And in the case of a metal base material part of a face-centered cubic iron material, 8 to 20 mass% of Na2O is mixed in the glass material.
[0053] The upper limit of the admixture ratio of Na2O is the range of the thermal expansion coefficient of the material of the individual metal substrate parts such as the metal substrate part of the body-centered cubic iron material or the metal substrate part of the face-centered cubic iron material as the thermal spraying object. In particular, when the admixture ratio of Na2O is more than 20% by mass, as Na2O volatilizes, the composition of the thermal sprayed glass part itself after thermal spraying changes greatly, and the thermal sprayed glass part is likely to become the cause of peeling or cracking from the surface of the metal substrate part. In addition, the glass material melts in the thermal spraying device described later and becomes filamentous, which hinders uniform thermal spraying. In addition, in the case of the thermal sprayed glass part formed by the glass material containing a large amount of Na2O, the corrosion resistance and hardness (wear resistance) are easily reduced. In addition, when the admixture ratio of Na2O is lower than the lower limit, the characteristics of increasing the viscosity when melting while improving the fusibility of the glass material are not observed, and the desired electrical insulation and voltage resistance cannot be obtained.
[0054] The components of B2O3, Li2O, and Na2O contained in the second component (B) are components that are relatively easy to volatilize when the glass material is heated during plasma thermal spraying. When a thermal sprayed glass portion derived from a molten glass material is formed on the surface of the metal substrate portion, the involvement of bubbles is inevitable. Therefore, as the characteristics of the glass material used in the metal glass composite of the embodiment, it is required to exert the function generated by the second component (B), be consistent with the composition of the glass material considering the thermal expansion coefficient of the material of the metal substrate portion, and achieve the suppression of the amount of bubbles generated in the thermal sprayed glass portion. If the amount of bubbles in the thermal sprayed glass portion is too much, the thermal sprayed glass portion itself will lose density, which is likely to cause a decrease in local strength. In addition, due to the change in the dielectric constant of the thermal sprayed glass portion, insulation breakdown is likely to occur.
[0055] Therefore, in the glass material used in the metallic glass composite of the embodiment, when combined as the second component (B), in the case of a metal base material portion of a body-centered cubic iron material, the second component (B) is blended in an amount of 18 to 30% by mass in total in the glass material. In addition, in the case of a metal base material portion of a face-centered cubic iron material, the second component (B) is blended in an amount of 25 to 35% by mass in total in the glass material.
[0056] The third component (C) is a component added mainly for the purpose of assisting the formation of glass quality of the thermal sprayed glass part produced after thermal spraying. The third component (C) is a component containing BaO, TiO2, Al2O3, and ZnO.
[0057] BaO is a component that assists SiO2 in glass material to form glass. The more the amount of BaO added increases, the more the fusibility of the glass material improves, and the more the softening temperature of the glass material during thermal spraying decreases. Wherein, although the effect is small compared with the viscosity rise produced by Na2O, the admixture of BaO can improve the adhesion strength of the glass material thermally sprayed on the surface of the metal substrate portion. Thus, BaO improves the smoothness of the glassy film of the thermal sprayed glass portion formed after plasma thermal spraying. Thus, BaO helps to thin the film thickness of the formed thermal sprayed glass portion, and improves the electrical insulation, withstand voltage, and relative dielectric constant of the formed thermal sprayed glass portion. If BaO is the same amount of admixture as the alkali components such as Li2O and Na2O, the electrical insulation and withstand voltage of BaO are more excellent than Li2O, Na2O, etc.
[0058] Therefore, in the case of a metal substrate portion of an iron material of a body-centered cubic system, 0 to 15% by mass of BaO is mixed into the glass material. And, in the case of a metal substrate portion of an iron material of a face-centered cubic system, 3 to 12% by mass of BaO is mixed into the glass material. When the mixing ratio of BaO in the glass material exceeds the upper limit, the viscosity of the glass of the thermally sprayed glass portion becomes extremely high when the glass material is subjected to plasma thermal spraying. As a result, the molten glass material melts in the thermal spraying device described later and becomes filamentary, which hinders uniform thermal spraying. Even in the film of the thermally sprayed glass portion formed after thermal spraying, the corrosion resistance and the like are reduced, and it becomes brittle over time. In the case of a metal substrate portion of an iron material of a body-centered cubic system, the lower limit of the mixing ratio of BaO can also be set to no mixing (0% by mass). Preferably, as with the metal substrate portion of an iron material of a face-centered cubic system, the lower limit of the mixing ratio of BaO is 3% by mass. This is because, although it depends on the amount of other components added, it is considered to improve the electrical insulation, withstand voltage, relative dielectric constant, etc. of the formed thermal sprayed glass part and to increase the adhesion strength of the glass film on the surface of the coated object.
[0059] TiO2 is a component that assists the glass formation of SiO2 in the glass material. The more the amount of TiO2 added increases, the higher the hardness (wear resistance) of the glass film of the thermal sprayed glass part formed. In addition, TiO2 also improves corrosion resistance, electrical insulation, and voltage resistance. TiO2 increases the viscosity of the glass material after thermal spraying. Therefore, in the case of a metal substrate part of an iron material of the body-centered cubic system, 2 to 15% by mass of TiO2 is added to the glass material. In addition, in the case of a metal substrate part of an iron material of the face-centered cubic system, 4 to 15% by mass of TiO2 is added to the glass material.
[0060] When the admixture ratio of TiO2 is lower than the upper limit, when the glass material melted by the heating of plasma thermal spraying is cooled (cooled) to become a thermal sprayed glass part, the crystallization of glass will be caused. That is, the thermal expansion coefficient becomes smaller, which easily induces peeling. The crystallization of glass will greatly reduce hardness, corrosion resistance, etc. When the admixture ratio of TiO2 is lower than the lower limit, although it depends on the admixture amount of other components, it will be difficult to show the improvement of the electrical insulation, voltage resistance, relative dielectric constant, etc. of the formed thermal sprayed glass part, and the melting property during the melting of plasma thermal spraying.
[0061] Al2O3 is a component that assists the glass formation of SiO2 in the glass material. Al2O3 has the effect of improving the corrosion resistance, hardness (wear resistance), electrical insulation, voltage resistance, etc. of the glass film of the thermal sprayed glass part formed by the molten glass material, and preventing recrystallization. It can be said that in order to improve the recrystallization of the glass of the thermal sprayed glass part caused by the presence of Li2O, it is also desirable to mix Al2O3. Therefore, in the case of the metal substrate part of the iron material of the body-centered cubic system, 0 to 8% by mass of Al2O3 is mixed in the glass material. And, in the case of the metal substrate part of the iron material of the face-centered cubic system, 0 to 5% by mass of Al2O3 is mixed in the glass material. When the mixing ratio of Al2O3 exceeds the upper limit, the solubility of the glass material during plasma thermal spraying will be reduced, making the viscosity extremely high. The lower limit of the mixing ratio of Al2O3 can also be unmixed (0% by mass), preferably 2% by mass. The addition of Al2O3 can improve the corrosion resistance of the thermal sprayed glass and prevent recrystallization.
[0062] ZnO is a component that assists SiO2 in the glass material to form a glassy substance. As with BaO, the more the admixture of ZnO increases, the more the fusibility of the glass material improves, and the more the softening temperature of the glass material during thermal spraying decreases. However, although the effect is smaller than the viscosity rise effect produced by Na2O, the admixture of ZnO can improve the adhesion strength of the thermal sprayed glass portion thermally sprayed to the surface of the metal substrate portion. Thus, as with BaO, ZnO helps to improve the smoothness of the glassy film of the thermal sprayed glass portion formed after plasma thermal spraying, and thins the film thickness of the glassy film of the thermal sprayed glass portion. Moreover, the electrical insulation, withstand voltage, and relative dielectric constant of the glassy film of the formed thermal sprayed glass portion can be improved. If ZnO is the admixture of the same amount of alkali components such as Li2O and Na2O, the electrical insulation and withstand voltage of Li2O, Na2O, etc. are more excellent.
[0063] In the case of a metal substrate portion of an iron material of a body-centered cubic system, 0 to 15% by mass of ZnO is mixed into the glass material. In addition, in the case of a metal substrate portion of an iron material of a face-centered cubic system, 0 to 5% by mass of ZnO is mixed into the glass material. When the mixing ratio of ZnO exceeds the upper limit, the viscosity of the glass material in a molten state when the glass material is subjected to plasma thermal spraying becomes high. As a result, the glass material in a molten state melts in the thermal spraying device described later and becomes filamentous, which hinders uniform thermal spraying. Even in the glass of the thermally sprayed glass portion formed after thermal spraying, the glass crystallization is caused, so the thermal expansion coefficient may be reduced to induce peeling. As a result, the corrosion resistance of the glass film of the thermally sprayed glass portion is reduced, and it becomes brittle over time. In particular, the crystallization of the glass cannot be controlled. The lower limit of the mixing ratio of ZnO can be set to non-mixed (0% by mass) regardless of the metal substrate portion of the iron material of the body-centered cubic system and the face-centered cubic system. 2% by mass is preferred. Although it depends on the amount of other components, it is likely to contribute to improving the electrical insulation, withstand voltage, relative dielectric constant, etc. of the glass of the thermal sprayed glass portion formed after thermal spraying, and to improving the adhesion strength of the glass on the surface of the coated object.
[0064] The purpose of the third component (C) is to improve the glass properties of the thermally sprayed glass portion produced after thermal spraying. Therefore, depending on the purpose, function, etc. of the metallic glass composite, it is allowed not to incorporate the components contained in the third component (C), as described above. In addition, the blending ratio of the third component (C) can be increased or decreased according to the balance with the first component (A) and the second component (B) and the adjustment of the thermal expansion coefficient. Therefore, in the glass material used in the metallic glass composite of the embodiment, when combined as the third component (C), in the case of a metal substrate portion of an iron material of a body-centered cubic system, a total of 10 to 30% by mass of the third component (C) is blended into the glass material. In addition, in the case of a metal substrate portion of an iron material of a face-centered cubic system, a total of 10 to 20% by mass of the third component (C) is blended into the glass material.
[0065] In the glass material used in the metallic glass composite of the embodiment, the main component (D) is the total of the first component (A), the second component (B) and the third component (C). The main component (D) in the glass material is 90% by mass or more. The entire glass material except for impurities inevitably mixed in can be made into only the main component (D). In addition, in consideration of the use and durability of the metallic glass composite, an auxiliary component (E) is further mixed into the main component (D).
[0066] The auxiliary component (E) is added to the glass material composed of the oxide species of the main component (D) for the purpose of enhancing and adding thermal spraying ease, stabilizing the properties of the glass quality of the glass material during melting and the glass coating of the thermal sprayed glass part, and improving the function. From the viewpoint of compositional balance, the auxiliary component (E) is contained in the glass material in an amount of 0 to 10% by mass. The components contained in the auxiliary component (E) are shown separately according to their functions.
[0067] CaO improves corrosion resistance, hardness (wear resistance), etc. In addition, CaO improves the fusibility of the glass material during thermal spraying and reduces the softening temperature of the glass material during thermal spraying. Therefore, the adhesion strength of the glass material thermally sprayed to the surface of the metal substrate portion can be improved. In the presence of BaO, the transparency of the glass film of the thermal sprayed glass portion is improved by a trace amount of CaO. In addition, although it depends on the blending ratio with other alkali components, when CaO is excessive, the corrosion resistance and hardness will be reduced, and the fusibility during thermal spraying will also deteriorate.
[0068] SrO improves the melting property of the glass material during thermal spraying and reduces the softening temperature of the glass material during thermal spraying. Therefore, the adhesion strength of the glass material thermally sprayed on the surface of the metal substrate portion can be improved. SrO is not easy to volatilize during thermal spraying, but if added in excessive amounts, it induces crystallization during the slow cooling of the thermally sprayed glass portion and becomes a cause of peeling.
[0069] MgO, P2O5, K2O, V2O5, MnO2, Fe2O3, Co3O4, NiO2, CuO, MoO3, SnO2, PbO, BiO2, and Lu2O3 improve the melting property of the glass material during thermal spraying and reduce the softening temperature of the glass material during thermal spraying. Therefore, the adhesion strength of the glass material thermally sprayed to the surface of the metal substrate can be improved. However, depending on the amount, the corrosion resistance, hardness (wear resistance), electrical insulation, and withstand voltage may be reduced, or the viscosity of the glass during thermal spraying may be sharply increased.
[0070] Cr2O3, ZrO2, and WO3 increase the hardness (wear resistance) of the glass film of the thermal sprayed glass part. Among them, ZrO2 improves corrosion resistance, electrical insulation, and voltage resistance. Sb2O3 has the effect of reducing and shrinking the amount of bubbles in the glass material that is thermally sprayed and adhered to the surface of the metal substrate part. However, depending on the amount of addition, ZrO2 and Sb2O3 sometimes cause the viscosity of the glass to rise sharply during melting.
[0071] Y2O3, Nb2O5, Ta2O3, Bi2O3, La2O3, CeO2, Pr6O 11 , Nd2O3, Sm2O3, and Gd2O3 improve the electrical insulation and withstand voltage of the thermally sprayed glass portion formed on the surface of the metal substrate portion. However, depending on the amount of content, the melting temperature of the glass material may rise and the meltability during thermal spraying may decrease. In addition, it may cause a sharp increase in the viscosity of the glass material during melting.
[0072] Figure 1 The preparation of the metal glass composites 1A, 1B, 1C, and 1D disclosed in the schematic diagrams (A) to (D) is roughly carried out in the following order. First, a metal substrate portion to be thermally sprayed is prepared. Then, the surface of the metal substrate portion is sandblasted. When sandblasting is performed, fine particles such as Al2O3 (aluminum oxide powder; al undum) and SiC (silicon carbide; carborundum) are sprayed onto the surface of the metal substrate portion. The surface of the metal substrate portion is roughened by sandblasting, which can improve the heat conduction to the metal substrate portion during the following heating. In addition, the implementation of the sandblasting is arbitrary and can be selected according to the shape of the metal substrate portion and the thermal spraying location.
[0073] The surface temperature of the metal substrate is heated to 200 to 1000°C, preferably 500 to 1000°C, and more preferably 700 to 1000°C. An electric heating furnace is used for heating. Heating is to keep the glass material in a molten state before the following thermal spraying. In addition, when the metal substrate is at room temperature, the adhesion of the molten glass material on the metal substrate is extremely reduced.
[0074] During thermal spraying, a plasma thermal spraying device described in Patent Document 2 or the like is used. The glass material is a glassy powder (frit) containing the aforementioned components. The glass material is supplied to the plasma thermal spraying device as a powder, and in the presence of a carrier gas, it is instantly melted in the plasma thermal spraying device, and sprayed onto the surface of the heated metal substrate portion to adhere to the surface. The amount of spraying on the surface of the metal substrate portion and the number of thermal spraying are increased or decreased to adjust the thickness of the glassy film of the thermally sprayed glass portion. In the embodiments described below, argon gas or dry air is used as the carrier gas.
[0075] The thickness of the glass film of the thermal sprayed glass portion can be set within a wide range of 10 to 2000 μm. For example, in a printing roller, the thickness of the glass film is set to a thickness of 1000 to 2000 μm. Also, in the case of an electrode for silent discharge, the thickness of the glass film is set to a thickness of 300 to 1500 μm. Also, in the case of a bolt, the thickness of the glass film is set to a thickness of 10 to 100 μm. Of course, these thicknesses are illustrative, and the thickness can be increased or decreased in consideration of the purpose, durability, etc.
[0076] After thermal spraying, the thermal sprayed glass part formed on the surface of the metal substrate is slowly cooled or air-cooled. Then, the surface is polished or ground as needed to make the surface smooth. Figure 1 The metallic glass composites 1A, 1B, 1C, 1D, etc. disclosed in the schematic diagrams (A) to (D) of FIG.
[0077] In order to continue to maintain the strong adhesion between the metal substrate and the thermal sprayed glass, the thermal expansion coefficients of the metal substrate and the thermal sprayed glass are kept consistent. As described above, during the cooling after thermal spraying, the metal substrate and the thermal sprayed glass shrink at the same time. However, due to the difference in expansion coefficients, the degree of volume shrinkage is different, resulting in poor adhesion such as a gap between the metal substrate and the thermal sprayed glass or cracks in the thermal sprayed glass.
[0078] The linear expansion coefficient of the metal base material of the body-centered cubic iron material, for example, SUS409, is 9.9 (×10 6 / ℃), the linear expansion coefficient of SS400 is 12(×10 6 Therefore, the glass material used as the material of the thermal sprayed glass portion has a linear expansion coefficient of 9 to 11 (×10 6 / ℃) range.
[0079] The linear expansion coefficient of the metal base material of the face-centered cubic iron material, for example, SUS304, is 17.3 (×10 6 Therefore, the glass material used as the material of the thermal sprayed glass portion has a linear expansion coefficient of 14 to 17 (×10 6 / ℃) range.
[0080] When adjusting the thermal expansion coefficients of the metal substrate part and the thermally sprayed glass part (glass material), in addition to the adjustment corresponding to the type of the metal substrate part described above, the difference in linear expansion coefficient between the metal substrate part and the thermally sprayed glass part (glass material) is also adjusted to be smaller. Specifically, the difference between the linear expansion coefficient of the glass material and the linear expansion coefficient of the metal substrate part is set within 15%. In theory, the linear expansion coefficients of both parties can be completely consistent (the difference is 0%). However, in the case of the shape of the metal substrate part such as a curved surface, the contraction force of the thermally sprayed glass part formed after plasma thermal spraying can be used to make the thermally sprayed glass part more firmly adhere to the surface of the metal substrate part.
[0081] The metal glass composite corresponding to the type of metal substrate portion can be exemplified as follows. As an iron system, rollers for conveying (roll / roller) and plywood for building materials can be cited. As an alloy (stainless steel system), water bucket rollers for printing devices, rollers in galvanizing baths, various rollers (roll / roller) used at room temperature, various rollers (roll / roller) for heating furnaces, electrodes for ozone-generating silent discharge bodies, electrodes for plasma generation, etc. can be cited. As a nickel alloy, various metal setsters for calcining sintered bodies can be cited. As a chromium-molybdenum steel alloy (such as SCM435, etc.), vehicle-mounted bolts (especially for fastening different types of metals, fastening components that generate sparks due to friction and static electricity) / bolts for fastening various components of wind power generation (especially bolts for offshore wind power generation), bolts for common mechanical devices, etc. can be cited.
[0082] In the metallic glass composite of the embodiment, as Figure 2 As shown in the cross-sectional schematic diagram of (B), a molten solidified portion 40 in which the thermal sprayed glass portion is embedded in the metal substrate portion is formed at the boundary portion 30 between the metal substrate portion 10 and the thermal sprayed glass portion 20 in the cross section. In addition, the molten solidified portion 40 is formed with a thickness of 0.3 μm or more. Bubbles 21 exist in the thermal sprayed glass portion 20, and residual glass 22 exists in the metal substrate portion 10 of the molten solidified portion 40. The symbol T30 in the figure is a mark indicating a 30% area in the thickness direction of the thermal sprayed glass portion 20 starting from the boundary portion 30.
[0083] As a point to be noted in the metal glass composite of the embodiment, the molten glass material thermally sprayed on the metal substrate does not simply adhere (accumulate) on the surface of the metal substrate. Specifically, it was confirmed by observation with a scanning electron microscope (SEM) that the heated metal substrate and the molten glass material are mixed together in the surface layer of the metal substrate (the boundary between the two sides), and a part of the molten glass material penetrates into the metal substrate (refer to Figure 3 As a result, after cooling, a molten solidified portion is generated in which the thermal sprayed glass portion is embedded in the metal base material portion.
[0084] In the metal glass composite of the embodiment, at the boundary between the metal substrate and the thermal sprayed glass, the thermal sprayed glass not only adheres to the metal substrate but also appropriately penetrates into the metal substrate, thereby forming a portion where the materials of both sides are mixed together. Therefore, compared with the conventional simple adhesion based on thermal spraying, the adhesion strength of both sides is improved due to the penetration of the thermal sprayed glass into the metal substrate. Specifically, the durability confirmed in the test of the falling ball height described later can be obtained.
[0085] The reason why the molten solidified portion is formed in the metal glass composite of the embodiment is believed to be due to the conditions of plasma thermal spraying that melts the glass material and sprays it onto the heated metal substrate portion. The molten glass material itself is also at a high temperature, so the surface portion of the metal substrate portion is further heated by its own heating and the heat generated by the molten glass material, so that the metal also melts in the surface portion of the metal substrate portion. In addition, it is believed that with the ejection force (speed, pressure) from the plasma thermal spraying, the molten glass material collides with the surface portion of the metal substrate portion, so that both are in a molten state within an extremely limited range, and therefore are easily mixed with each other, and finally a molten solidified portion is formed.
[0086] In the case of Patent Document 1 (Japanese Patent Application Laid-Open No. 2013-216977), a molten glass material infiltrates the surface of the metal substrate roughened by sandblasting. In contrast, the metallic glass composite of the embodiment is different in structure in that a molten solidified portion is formed.
[0087] Figure 3The electron microscope photos taken later are cross-sections of the trial examples of the metal glass composite. In particular, based on the measurement of the photos with increased magnification based on (B) of each figure, it is confirmed that the molten solidified portion is more than 0.3 μm thick. As for the upper limit of the molten solidified portion, it is impossible to exceed the thickness of the entire thermal sprayed glass portion. Therefore, it is believed that the upper limit of the molten solidified portion is a thickness of approximately 1 μm or less. As can be understood from each photo, in the metal glass composite of the embodiment, the boundary portion is the interface where the thermal sprayed glass portion contacts the metal substrate portion. The molten solidified portion is the portion where the glass material is sealed in the metal substrate portion and dispersed, and is the depth from the boundary portion between the metal substrate portion and the thermal sprayed glass portion to the range where the sealed glass material exists.
[0088] The description so far discloses the composition of both the thermal sprayed glass part (glass material) and the metal substrate part, the relationship of the thermal expansion coefficient, and the characteristics of the molten solidification part generated at the boundary part. In addition, it is necessary to make regulations after the thermal sprayed glass part is formed on the surface of the metal substrate part. Specifically, it is necessary to control the amount of bubbles present in the thermal sprayed glass part. Therefore, the area ratio of bubbles larger than 1 μm in the cross section in the thickness direction of the thermal sprayed glass part in the formed metal glass composite is suppressed to less than 40%. When measuring bubbles, the metal glass composite is cut in the thickness direction of the thermal sprayed glass part to expose the cut surface. Therefore, the cut surface is enlarged using a scanning electron microscope (SEM) to find the area of bubbles larger than 1 μm in diameter in the exposed cut surface. Then, the total area of bubbles larger than 1 μm in diameter is calculated. The area ratio of bubbles larger than 1 μm is calculated based on the total area of bubbles occupied in the area of the cut surface of the thermal sprayed glass part. That is, the area ratio of bubbles larger than 1 μm is calculated as “area ratio of bubbles larger than 1 μm (%)”={(total area of bubbles larger than 1 μm in the cut surface) / (total area of the cut surface)}×100.
[0089] If the amount of bubbles in the thermal sprayed glass part of the metallic glass composite increases, the thermal sprayed glass part approaches the so-called sponge state, loses density, and the structural strength decreases. As shown in the test of the falling ball height described later, the higher the area ratio of bubbles in the cut surface, the lower the strength against impact. Therefore, it is an indicator that directly affects the durability of the metallic glass composite, so the area ratio of bubbles larger than 1 μm in the cross section in the thickness direction of the thermal sprayed glass part is less than 40%, preferably less than 30%, and more preferably less than 20%.
[0090] Furthermore, when an electrode is envisioned as a use of a metal glass composite, if the area ratio of bubbles becomes high, insulation breakdown or the like is likely to occur in the thermally sprayed glass portion when power is applied. This may cause damage to the equipment on which the metal glass composite is mounted. Therefore, it is important to suppress the area ratio of bubbles as much as possible. As described in the composition of the glass material, when the glass material is melted by heating during thermal spraying, the second component (B) is easily volatilized, and at this time, bubbles are generated by gasification. Furthermore, during thermal spraying, the molten glass material is instantly coated on the surface of the metal substrate portion and adheres to the surface. The bubbles generated in the molten glass material cannot move, and the bubbles are directly cooled in a state of being sealed in the thermally sprayed glass portion, and remain in the thermally sprayed glass portion.
[0091] From the viewpoints of adjusting the thermal expansion coefficient with the metal substrate part and improving the durability of the glass, the first component (A), the second component (B) and the third component (C) of the glass material need to have a blending ratio. Therefore, even if it is known that it is vaporized, the second component (B) must be blended. It can be understood that the composition of the glass material of the embodiment is established in terms of achieving a balance between adjusting the thermal expansion coefficient with the metal substrate part and suppressing the residual bubbles from the viewpoint of durability.
[0092] In the metal glass composite of the embodiment, the basic existence area and area ratio are also specified in detail. Specifically, at the boundary of the metal substrate part and the thermal sprayed glass part in the longitudinal cut surface of the metal glass composite, the area ratio of bubbles larger than 1 μm existing in the area within 30% in the thickness direction of the thermal sprayed glass part starting from the boundary is preferably suppressed to less than 50%. Moreover, it is preferred that the thickness of the thermal sprayed glass part is in the range of 10 to 100 μm, and the area ratio of bubbles larger than 1 μm in the cross section in the thickness direction of the thermal sprayed glass part is less than 10% in the thermal sprayed glass part.
[0093] As described above, when the glass material is thermally sprayed, the components are volatilized and vaporized by the heating of the thermal spraying. Moreover, the glass material in the molten state is sprayed before the volatilized gas diffuses, so it will remain in the form of bubbles. In particular, in the deep area of the thermally sprayed glass part in the metal glass composite, in other words, in the area close to the metal substrate part, the bubbles are inevitably easy to increase. In addition, in order to improve the adhesion strength between the thermally sprayed glass part and the metal substrate part, it is preferred that the thermally sprayed glass part is dense, that is, it is preferred that there are fewer bubbles.
[0094] Therefore, in order to grasp the morphology of the thermal sprayed glass part, the area ratio of bubbles larger than 1 μm is suppressed to 50% or less, preferably to 40% or less, in the region up to 30% (including 30%) in the thickness direction of the thermal sprayed glass part starting from the boundary part. By suppressing the amount of bubbles near the boundary part of the thermal sprayed glass part, the density of the thermal sprayed glass part near the boundary part is improved, and the strength is easily increased.
[0095] Moreover, in the metallic glass composite, the thickness of the thermal sprayed glass portion can be increased or decreased according to the application and based on the thermal spraying amount. However, the thickening of the thermal sprayed glass portion will lead to an increase in glass quality, which may cause cracking after cooling and reduce durability during use. In particular, when the purpose is corrosion protection, insulation, etc., it can be said that the thinner the thickness, the better. Therefore, the thermal sprayed glass portion is finished to a thickness in the range of 10 to 100 μm.
[0096] In a thermal sprayed glass portion of such thickness, the presence of bubbles itself is directly related to the reduction of durability, insulation and other performances, so it is preferable to further reduce the bubbles compared with the above conditions. Therefore, the area ratio of bubbles larger than 1 μm is suppressed to less than 10% in the thermal sprayed glass portion (the entire cross section), preferably suppressed to less than 7%.
[0097] Example
[0098] [Type of metal base material]
[0099] When preparing the metallic glass composite, the following three types of metal substrate plate bodies (100 mm × 30 mm, thickness 1.2 mm) were used. As the metal substrate composed of body-centered cubic iron material, SUS409, SUS430, and SS400 were used. As the metal substrate composed of face-centered cubic iron material, SUS304 was used. For reference, the metal composition (mass %) and the linear expansion coefficient (×10 -6 / °C) are shown in Table 1. Each metal in the table is an iron-based alloy, and therefore Fe is shown as the remainder.
[0100] [Table 1]
[0101]
[0102] [Metal base material treatment]
[0103] The plate-like bodies of each metal substrate part listed in Table 1 were sandblasted with #60 and #80 alumina powder, and the surface was air-cleaned to remove dust. Before thermal spraying, the plate-like bodies were heated to about 700 to 1000° C. in an electric heating furnace, and thermal spraying was performed under the conditions described below before the temperature was lowered.
[0104] [Composition of glass material]
[0105] The glass materials of trial examples 1 to 16 were prepared by blending the components in the composition of Table 2 below, and crushed to form a frit (powder). The frit was graded into the desired average particle size. In the table, each component is set as the mass % (mass %) of the entire glass material. In addition, from the perspective of easy understanding, the total of the second component (B) and the total of the third component (C) in the entire glass material are also stated. In addition, the linear expansion coefficient (α) of each trial example is stated (unit: ×10 -6 / ℃).
[0106] [Table 2]
[0107]
[0108] [Thermal spraying equipment / thermal spraying conditions]
[0109] During plasma thermal spraying, a thermal spraying device was used, which was a product name "Model SG-100 Plasma Spray Gun" manufactured by Praxair Technology, Inc. In addition, a product name "Model 3710 Plasma Control Console" manufactured by Praxair Technology, Inc. was used as a device for controlling the supply of electricity, cooling water, and gas, and the supply of thermal spraying materials. A product name "Model 1264 Powder Feeder" manufactured by Praxair Technology, Inc. was used as a supply device for glass materials. A product name "Model PS-1000 Plasma Power Source" manufactured by Praxair Technology, Inc. was used as a power supply device. A product name "Model HF-2200" manufactured by Praxair Technology, Inc. was used as a high-frequency generator.
[0110] During thermal spraying, the glass material frits of Trial Examples 1 to 16 were thermally sprayed in the same manner. However, during thermal spraying, the speed of scanning the plate-like body of the metal substrate was increased or decreased to increase or decrease the amount of adhesion to the surface accompanied by spraying.
[0111] Thermal spraying conditions
[0112] Voltage: 30~50V
[0113] Current: 700~1000A
[0114] Heating temperature of metal substrate: 700~1000℃
[0115] Regarding each thermal spraying condition, if it is below the lower limit, the influence of insufficient heat is large, the glass material will not melt on the surface of the metal substrate, and adhesion cannot be ensured. And if it exceeds the upper limit, the melting of the metal substrate is too strong, and the shape of the metal substrate itself will be deformed.
[0116] The raw material supply conditions were the following gas types and flow rates.
[0117] The carrier gas for the raw materials was set to dry air or argon.
[0118] When the flow rate is Fa (NL / min) and the raw material supply rate is Fb (g / min), "Fb / Fa" is controlled to be less than 0.4. If "Fb / Fa" exceeds 0.4, even if the thermal spraying conditions described above are met, the base is not easily melted.
[0119] [Characteristics of Metallic Glass Composites]
[0120] As metal glass composites with a metal substrate composed of a body-centered cubic iron material, trial examples G1 to G21 were prepared, and as metal glass composites with a metal substrate composed of a face-centered cubic iron material, trial examples H1 to H8 were prepared. The results of trial examples G1 to G21 are shown in Table 3, and the results of trial examples H1 to H8 are shown in Table 4.
[0121] In Tables 3 and 4, the codes of the trial examples, the types of glass materials disclosed in Table 2, the types of metal substrates, the heating temperature of the metal substrates (°C), the current during thermal spraying (A), the thickness of the thermal sprayed glass portion of the metal glass composite finally formed (μm), the area ratio of bubbles larger than 1 μm in the entire thermal sprayed glass portion (%), the area ratio of bubbles larger than 1 μm existing in an area within 30% in the thickness direction of the thermal sprayed glass portion starting from the boundary portion (%), the thickness of the molten solidified portion (μm), the maximum diameter of bubbles existing in the thermal sprayed glass portion (μm), the ball drop height (cm), and the dielectric withstand voltage test (MV / m).
[0122] When observing and measuring the thickness and bubbles, the metallic glass composite of each trial example was cut longitudinally and observed using a scanning electron microscope (SEM). Figure 3 This is an electron microscope photograph of the prototype code G1. Figure 4 This is an electron microscope photograph of the prototype code G2. Figure 5 This is an electron microscope photo of the prototype code G6. Figure 6 This is an electron microscope photo of the prototype code G11. Figure 7 This is an electron microscope photo of the prototype code G13. Figure 8 This is an electron microscope photo of the prototype code G19 and Fig. 9 The electron microscope photographs of the prototype code H5 are shown in Figures (A) and (B) respectively. The electron microscope photographs are shown in Figures (A) and (B) respectively.
[0123] In the evaluation of the drop ball height, a 150 g steel ball was freely dropped from directly above the thermal sprayed glass portion (glassy exposed surface) of the metallic glass composite of each trial example. At this time, the height (vertical length from the thermal sprayed glass portion to the steel ball) at which visual appearance abnormalities such as cracks, cracks (cracks), and breakage can be confirmed in the thermal sprayed glass portion due to the impact of the falling steel ball was set as the drop ball height of the trial example. Fig.10 The plotted graph (scatter diagram) shows the relationship between the total bubble area ratio (%) and the ball drop height (cm) in the thermal sprayed glass portion of the metallic glass composite of each trial example.
[0124] Dielectric Strength Test The dielectric strength test was conducted in accordance with the test method of JIS C 2110 (2016) (IEC 60243-1: 2013) and the metallic glass composite of each trial example was measured. Fig.11 The plotted graph (scatter diagram) shows the relationship between the bubble area ratio (%) and the dielectric strength (MV / m) of the boundary portion in the thermal sprayed glass portion of the metallic glass composite of each trial example. The insulation withstand voltage test was conducted using a model: HP-5110DS manufactured by Nippon Technart Inc., and the presence or absence of leakage was evaluated by applying 10 kV for 1 minute.
[0125] For the metallic glass composites of Trial Examples G1 to G19 in Table 3, the moving speed of the thermal spraying device was set to 31 mm / sec, and for Trial Examples G1 to G18, the metal substrate portion was thermally sprayed 5 times, and for Trial Example G19, it was thermally sprayed once. For Trial Example G20, the moving speed of the thermal spraying device was set to 52 mm / sec and thermally sprayed once. For Trial Example G21, the moving speed of the thermal spraying device was set to 125 mm / sec and thermally sprayed once.
[0126] The metallic glass composites of Trial Examples H1 to H8 in Table 4 were thermally sprayed five times on the metal substrate portion while setting the moving speed of the thermal spraying device to 31 mm / sec.
[0128] For the metallic glass composites of trial examples H9 to H16 in Table 5, the moving speed of the thermal spraying device was set to 125 mm / sec and the metal substrate portion was thermally sprayed once. For the metallic glass composites of trial examples H17 to H21, the moving speed of the thermal spraying device was set to 52 mm / sec and the metal substrate portion was thermally sprayed once. For the metallic glass composites of trial examples H22 to H24, the moving speed of the thermal spraying device was set to 31 mm / sec and the metal substrate portion was thermally sprayed 5 times.
[0129] [Table 3]
[0130]
[0131] [Table 4]
[0132]
[0133] [Table 5]
[0134]
[0135] [Results and Investigation]
[0136] According to Table 3, the metal glass composite of Trial Example G6 uses the glass material of Trial Example 4. In Trial Example 4, the proportion of the second component (B) as a volatile component is high (32% by mass in total). Therefore, the area ratio of bubbles increases. Due to the increase in voids caused by the increase in bubbles, the drop height deteriorates. In contrast, the metal glass composite of Trial Example G5 uses the glass material of Trial Example 3. The proportion of the second component (B) of the glass material of Trial Example 3 is a total of 29% by mass. In this way, it can be confirmed that the bubbles are reduced in the total bubble area ratio of Trial Example G5, and the increase in the drop height also becomes obvious. Therefore, for the metal substrate portion composed of the body-centered cubic iron material found in SUS409, it is inferred that the upper limit of the proportion of the second component (B) is 30% by mass.
[0137] The metallic glass composites of trial examples G19 to G21 are examples in which the glass film thickness of the thermal sprayed glass portion is reduced to less than 100 μm. For trial examples G19 to G21, the glass materials of trial examples 1 and 16 in which the proportion of the second component (B) is low are used. It is believed that the volatilization amount during thermal spraying is suppressed and the generation of bubbles is reduced. From the result of the falling ball height, it can be confirmed that an extremely strong thermal sprayed glass portion is formed.
[0138] When making the metal glass composite of each trial example, the thermal spraying environment of the plasma thermal spraying device is a temperature region in which the outermost surface of the metal substrate portion serving as the base for thermal spraying is melted. Therefore, due to the influence of heat during thermal spraying, the components of the glass material are more likely to volatilize. In particular, the linear expansion coefficient of the body-centered cubic iron material is lower than the linear expansion coefficient of the metal composed of the face-centered cubic iron material, and the control of the thermal expansion rate (linear expansion coefficient) and the suppression of the upper limit of the easily volatile second component (B) become more important. Therefore, according to the results of the trial examples, the blending ratio of the second component (B) in the glass material is 10 to 30% by mass, preferably 20 to 30% by mass.
[0139] The metallic glass composites of the trial examples H1 to H24 are examples of a metal substrate portion (SUS304) composed of a face-centered cubic iron material. In the case of a face-centered cubic iron material, the linear expansion coefficient is greater than the linear expansion coefficient of a body-centered cubic iron material, so the restriction on the blending ratio of the second component (B) is relaxed. In addition, the amount of bubbles is small overall, and the ball drop height is good. Therefore, the blending ratio of the second component (B) in the glass material is 25 to 35% by mass.
[0140] When preparing the glass material of the trial example, when SiO2 of the first component (A) in the glass material exceeds 70% by mass, the viscosity of the molten glass material becomes too high during thermal spraying, and the remaining bubbles become obvious. In addition, when it is less than 35% by mass, it is difficult to adjust the linear expansion coefficient. Therefore, in the case of the body-centered cubic iron material, SiO2 of the first component (A) in the glass material is 35 to 70% by mass. For the same reason, in the case of the face-centered cubic iron material, SiO2 of the first component (A) in the glass material is 50 to 60% by mass.
[0141] The third component (C) is a component that affects the viscosity of the glass material in the molten state. According to the results of the glass material and the metallic glass composite of each trial example, in the case of the body-centered cubic iron material, the total amount of the third component (C) in the glass material is 10 to 30% by mass, and in the case of the face-centered cubic iron material, the SiO2 of the first component (A) in the glass material is 10 to 20% by mass.
[0142] Considering the results of the ball drop height and dielectric strength of the metal glass composites of trial examples G1 to G19 and trial examples H1 to G24, the area ratio of bubbles larger than 1 μm in the cross section in the thickness direction of the thermal sprayed glass portion is less than 40%, preferably less than 30%. Moreover, the area ratio of bubbles larger than 1 μm existing in the region within 30% in the thickness direction of the thermal sprayed glass portion starting from the boundary portion is also preferably less than 50%. Moreover, in the example where the thickness of the thermal sprayed glass portion of the metal glass composites of trial examples G19 to G21 is less than 100 μm, the area ratio of bubbles larger than 1 μm existing in the thickness direction of the thermal sprayed glass portion can be made extremely small to less than 10%, thereby improving the performance of the ball drop height and dielectric strength.
[0143] by Fig.10 The plotted graph shows the relationship between the total bubble area ratio (%) and the ball drop height (cm). As the total bubble area ratio increases, the value of the ball drop height tends to decrease. This indicates that the increase in bubbles causes the strength of the thermal sprayed glass part to decrease. Fig.11 The plotted graph shows the relationship between the bubble area ratio (%) and the dielectric strength (MV / m) at the boundary. The dielectric strength can be maintained until the bubble area ratio at the boundary reaches 40%. However, from the point where the bubble area ratio at the boundary exceeds 40%, the decrease in dielectric strength becomes obvious. Based on this tendency, the range of the aforementioned bubble area ratio can be determined.
[0144] Explanation of symbols
[0145] 1A, 1B, 1C, 1D - Metallic glass composites
[0146] 10, 11, 12, 13, 14-Metal substrate
[0147] 20-Thermal spraying glass department
[0148] 21-Bubbles
[0149] 22-Residual glass
[0150] 30-Border Department
[0151] 40-Melting and solidification section
[0152] T30 - 30% area in the thickness direction of the thermally sprayed glass part.
Claims
1. A metallic glass composite, characterized in that: The invention comprises: a metal base material part, which is composed of a body-centered cubic iron material; and a thermal sprayed glass part, which is formed on the metal base material part with a film thickness of 10 to 2000 μm. In the glass material forming the thermal sprayed glass portion, As the first component (A), SiO2: 35-70% by mass As the second component (B), B2O3: 9-15 mass%, Li2O: 5-9 mass% and The total amount of Na2O: 4 to 10% by mass is set to 18 to 30% by mass, As the third component (C), BaO: 0-15 mass %, TiO2: 2-15% by mass, Al2O3: 0-8 mass% and The total amount of ZnO: 0 to 15 mass % is set to 10 to 30 mass %, As the main component (D) composed of the total of the first component (A), the second component (B) and the third component (C), 90% by mass or more is contained, The linear expansion coefficient of the glass material from room temperature to 300°C is 9 to 11 (×10 6 / ℃), The area ratio of bubbles having a size of 1 μm or larger in a cross section in the thickness direction of the thermally sprayed glass portion is less than 40%.
2. A metallic glass composite, characterized in that: The invention comprises: a metal base material part, which is composed of a face-centered cubic iron material; and a thermal sprayed glass part, which is formed on the metal base material part with a film thickness of 10 to 2000 μm. In the glass material forming the thermal sprayed glass portion, As the first component (A), SiO2: 50-60% by mass As the second component (B), B2O3: 2-8 mass %, Li2O: 8-15% by mass and The total amount of Na2O: 8 to 20 mass % is set to 25 to 35 mass %, As the third component (C), BaO: 3 to 12 mass %, TiO2: 4-15% by mass, Al2O3: 0-5 mass% and ZnO: 0 to 5 mass % is set to 10 to 20 mass %, As the main component (D) composed of the total of the first component (A), the second component (B) and the third component (C), 90% by mass or more is contained, The linear expansion coefficient of the glass material from room temperature to 300°C is 14 to 17 (×10 6 / ℃), The area ratio of bubbles having a size of 1 μm or larger in a cross section in the thickness direction of the thermally sprayed glass portion is less than 40%.
3. The metallic glass composite according to claim 1 or 2, wherein: A difference between the linear expansion coefficient of the glass material and the linear expansion coefficient of the metal base material portion is within 15%.
4. The metallic glass composite according to claim 1 or 2, wherein: The metallic glass composite includes a melt-solidified portion at a boundary between the metal base material portion and the thermal sprayed glass portion in the cross section, the thermal sprayed glass portion being embedded in the metal base material portion, and the melt-solidified portion having a thickness of 0.3 μm or more.
5. The metallic glass composite according to claim 1 or 2, wherein: In the thermal sprayed glass portion, an area ratio of bubbles of 1 μm or larger existing in a region within 30% of the thickness direction of the thermal sprayed glass portion starting from the boundary between the metal base material portion and the thermal sprayed glass portion in the cross section is 50% or less.
6. The metallic glass composite according to claim 1 or 2, wherein: The thickness of the thermal sprayed glass portion is 10 to 100 μm, and the area ratio of bubbles having a size of 1 μm or more in a cross section in the thickness direction of the thermal sprayed glass portion is less than 10%.
7. The metallic glass composite according to claim 1 or 2, wherein: The components other than the main component (D) in the glass material are auxiliary components (E), The auxiliary component (E) is CaO, SrO, MgO, P2O5, K2O, V2O5, Cr2O3, MnO2, Fe2O3, Co3O4, NiO2, CuO, Y2O3, ZrO2, Nb2O2, MoO3, SnO2, Sb2O3, WO3, PbO, Bi2O3, La2O3, CeO2, Pr6O 11 , any one or more of Nd2O3, Sm2O3, and Gd2O3.
Citation Information
Patent Citations
Vitreous flame spraying material for metal base roll body, metal base roll body with vitreous film, and ozonizer
JP2013216977A
Glass material thermal spray apparatus
JP2021130841A